1984
DOI: 10.1111/j.1559-1816.1984.tb02250.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Social Psychology to Induce Charitable Donations1

Abstract: As part of a door‐to‐door campaign to raise funds for the American Cancer Society, 359 people in a middle‐class neighborhood were randomly assigned to five different versions of a request for contributions. A version of the request similar to that typically used in such charity drives served as a control and the other four versions were modified slightly on the basis of social psychological principles. Three of these manipulations failed to increase donating beyond the level of the standard request. Replicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 9 publications
0
27
2
2
Order By: Relevance
“…Most studies find no reliable differences between males and females. A group of studies find that while females are more likely to give, males give higher amounts Bekkers 2004;Belfield & Beney 2000;CAF 2005;Jackson & Latané 1981;Lyons & Passey 2005;Sokolowski 1996;Weyant 1984). Two studies found that females ware more likely to give but do not give higher amounts than males (Lyons & Nivison-Smith 2006;Mesch et al 2006).…”
Section: Gendermentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies find no reliable differences between males and females. A group of studies find that while females are more likely to give, males give higher amounts Bekkers 2004;Belfield & Beney 2000;CAF 2005;Jackson & Latané 1981;Lyons & Passey 2005;Sokolowski 1996;Weyant 1984). Two studies found that females ware more likely to give but do not give higher amounts than males (Lyons & Nivison-Smith 2006;Mesch et al 2006).…”
Section: Gendermentioning
confidence: 99%
“…Obviously, higher income households donate higher amounts than lower income households (Abrams & Schmitz 1978;1984;Andreoni 1988;Andreoni & Miller 2002;Apinunmahakul & Devlin 2004;Auten et al 1992;Auten & Rudney 1990;Banks & Tanner 1999;Barrett 1991;Bekkers 2003;2006b;2007b;Bekkers & Schuyt 2005;Belfield & Beney 2000;Bielefeld et al 2005;Brooks 2002;Brooks 2005;Brown & Lankford 1992;Carman 2006;Chang 2005a;Choe & Jeong 1993;Chua & Wong 1999;Clotfelter 1980;Daneshvary & Luksetich 1997;Eaton 2001;Farmer & Fedor 2001;Feenberg 1987;Feldstein 1975a;1975b;Feldstein & Clotfelter 1976;Feldstein & Taylor 1976;Glenday et al 1986;Greenwood 1993;Gruber 2004;Havens et al 2007;Hood et al 1977;Houston 2006;Hrung 2004;James & Sharpe 2007;Jones & Posnett 1991a;1991b;Kingma 1989;…”
Section: Incomementioning
confidence: 99%
See 2 more Smart Citations
“…Так, в целом ряде зарубежных работ прослеживаются гендерные различия в рассматриваемой сфере [Odendah 1990;Havens, O'Herlihy, Schervish 2006]. Некоторые исследования показывают, что мужчи-ны жертвуют больше, в то время как женщины делают это чаще [Jackson, Latané 1981;Weyant 1984;Andreoni, Brown, Rischall 2003;Bekkers 2004;Giving UK 2005].…”
Section: рис 1 распределение ответов респондентов на вопрос: «за поunclassified